Upaya Meningkatkan Hasil Belajar IPAS Menggunakan Bahan Ajar Digital untuk Siswa - Suhendra, I Wayan; Arnyana, Ida Bagus Putu; Candiasa, I Made (Lembaga Sosial Rumah Indonesia, 2024)
Purpose – Covid-19 has had a negative impact on the education sector. Students' understanding of the lesson material becomes less in-depth. As a result, learning outcomes do not match expectations. However, students' diverse learning styles pose a challenge in increasing students' understanding of a lesson material. For this reason, innovation is needed that can accommodate various student learning styles. The solution is to develop digital-based teaching materials that are integrated with various media variants in them.Methods – This research and development aims to determine the design, validity, practicality and effectiveness of digital-based science and science teaching materials on cognitive learning outcomes for Class IV elementary school students. The development model used is the ADDIE development model which consists of 5 stages, namely analysis, design, development, implementation, and evaluation